Coronary Arterial Stenting in Acute Coronary Syndrome - S. O. Sokolova (Obŝaâ Reanimatologiâ, 2006)
To study the long-term results of coronary arterial stenting in relation to the baseline clinical and angiographic findings and the presence of acute coronary syndrome at the moment of a procedure, the authors made a retrospective comparison of groups of patients undergone balloon angioplasty with a stent being inserted. The findings indicate that while choosing the tactics of treatment for patients with coronary heart disease (CHD) and assessing the risk of development of poor outcomes of coronary stenting, it is necessary to take into account a combination of factors significantly affecting the occurrence of coronary events and the development of restenosis after surgery (smoking, acute coronary syndrome at the moment of a procedure, serum triglyceride levels, extent of coronary bed affliction, type of stenosis, diameter of a revas-cularized vessel) and to apply, where possible, the minimal effective exposure principle to achieve the optimal result of a procedure.